Sino-Poland intercollegiate cooperation in tertiary education: The case study of “Nicolaus Copernicus University 3 + 1 + 2 intercollegiate cooperation” project - Bu, Xiaochen; Zhang, Yi (Journal of Positive Management, 2022)
Purpose: This paper aims to identify the strengths and challenges of Sino-Poland intercollegiate cooperation in tertiary education projects and give recommendations for such cross-culture cooperation projects. Methodology/approach: This paper utilized qualitative study analysis that conducted and interpreted semi-structured in-depth individual interviews with Chinese students participating in "Nicolaus Copernicus University 3 + 1 + 2 intercollegiate cooperation" project. Data is coded and analyzed using sentiment analysis. Findings: The study shows that Sino-Poland intercollegiate cooperation is gradually developing, which has apparent strengths, including increased the number of Chinese students, promotion of Sino-Poland university cooperation, and creation of distinctive cooperation models. However, some of the challenges that have emerged include project overly seeking profit-oriented, the declining admission standards, and cultural differences in Sino-Poland tertiary education cooperation and competition from universities in other European countries. Implications: The results of the study give practical suggestions for Sino-Poland intercollegiate cooperation. As Sino-Poland intercollegiate cooperation is still in its infancy, Chinese and Poland universities should innovate their cooperation models in a cross-cultural context, enhance their communication, and publicize their projects extensively to promote mutual benefits. Simultaneously, the cooperation projects should not be profit-driven and lower the admissions standards because the cooperation projects' reputation is also crucial. Originality/value: The study contributes to the theory development on cross-cultural cooperation between Sino-Poland tertiary education, in particular, it offers insights into the challenges that arise in Sino-Poland intercollegiate cooperation projects and how to develop better cooperation models in the future so that Sino-Poland tertiary education cooperation can develop its own unique symbiotic culture and management model. Keywords: Sino-Poland, cross-culture cooperation, tertiary education, intercollegiate cooperation Paper type: Case study